Expanded carrier screening for preconception reproductive risk assessment: Prevalence of carrier status in a Mexican population. (27th February 2020) - Hernandez‐Nieto, Carlos; Alkon‐Meadows, Tamar; Lee, Joseph; Cacchione, Teresa; Iyune‐Cojab, Esther; Garza‐Galvan, Maria; Luna‐Rojas, Martha; Copperman, Alan B; Sandler, Benjamin
Abstract: Objective: Genetic carrier screening has the potential to identify couples at risk of having a child affected with an autosomal recessive or X‐linked disorder. However, the current prevalence of carrier status for these conditions in developing countries is not well defined. This study assesses the prevalence of carrier status of selected genetic conditions utilizing an expanded, pan‐ethnic genetic carrier screening panel (ECS) in a large population of Mexican patients. Methods: Retrospective chart review of all patients tested with a single ECS panel at an international infertility center from 2012 to 2018 were included, and the prevalence of positive carrier status in a Mexican population was evaluated. Results: Eight hundred five individuals were analyzed with ECS testing for 283 genetic conditions. Three hundred fifty‐two carriers (43.7%) were identified with 503 pathogenic variants in 145 different genes. Seventeen of the 391 participating couples (4.34%) were identified as being at‐risk couples. The most prevalent alleles found were associated with alpha thalassemia, cystic fibrosis, GJB2 nonsyndromic hearing loss, biotinidase deficiency, and familial Mediterranean fever. Conclusion: Based on the prevalence and severity of Mendelian disorders, we recommend that couples who wish to conceive regardless of their ethnicity background explore carrier screening and genetic counseling prior to reproductive medical treatment.